Population Policies and Implementation in India: A Critical Analysis - Laddunuri, Madan Mohan (International Journal of Humanities and Education Development (IJHED), 2020)
This paper describes the developments and changes of the population policies and their implementations in India since the 1950s. It roughly divides the population policies and the implementations into three periods. The first is a service providing period between 1952 and 1961. The second is an imperative and target oriented period between 1962 and 1977. The third is a voluntary period since April 1977. The author concludes that India‟s population control is much less effective than the government expected. In the very traditional and highly diversified India society, family planning can be advocated and promoted, but cannot be forced. Therefore, a comprehensive socioeconomic development could be a more effective way in reducing the overpopulation problem.